Synthesis and characterization of Mn-DOPED ZnO nanoparticles - Tan, Tong Ling (Universiti Malaysia Sarawak, UNIMAS, 2012)
Mn-doped ZnO Nanoparticles has gained a lot of attention from the scientists and researchers to undergo this interest research due to its various applications in optoelectronic devices, chemical sensors, solar cells and photocatalyst. However, the doping efficiency was influenced by the strong tendency of the Mn dopant ions to segregate at the nanoparticles surfaces. Hence, many efforts have been made related to size, morphology and preparation on Mn-doped ZnO nanoparticles. In this project, coprecipitation method was used to synthesize Mn-doped ZnO nanoparticles. On the other hand, the effects of concentration of Mn dopant ions on the particle size, shape and optical properties of Mn-doped ZnO nanoparticles were investigated through Scanning Electron Microscope, Transmission Electron Microscope, Fourier Transform Infrared Spectroscopy, UV-Visible spectroscopy, Energy Dispersive X-rays and Fluorescence Spectrophotometer.